(untitled) (Research, Society and Development, 2021)
Introduction: Mobile technologies, especially smartphone applications, have contributed a lot in the area of health and physical activity, but there is an increasing concern with the validation criteria of these tools. It is extremely important to know if the physiological parameters used are safe and reliable to promote and monitor the practice of physical activity. With technological innovation, it is possible to process the data of accelerometer to measure energy expenditure. Objective: this study searched for evidence of scientific validation in Apps that uses smartphone’s accelerometer as energy expenditure indicator. Method: The keywords, inclusion and exclusion criteria were defined. The selected articles were categorized using an adapted questionnaire. Result: In a total of 1923 articles, eight articles meted all inclusion criteria that developed and validated apps for physical activity analysis. Conclusion: The results induced the effectiveness of smartphone’s accelerometer to recognize physical activity and energy expenditure. It can be used to encourage healthy and safe practices, leading to improvements in quality of life. The limited number of articles with scientifically validated Applications indicates the need for more research.